Δ(9)-Tetrahydrocannabinol decreases willingness to exert cognitive effort in male rats - Silveira, Mason M. (J Psychiatry Neurosci, 2017)
BACKGROUND: Acceptance of cannabis use is growing. However, prolonged use is associated with diminished psychosocial outcomes, potentially mediated by drug-induced cognitive impairments. Δ(9)-Tetrahydrocannabinol (THC) is the main psychoactive ingredient in cannabis, yet other phytocannabinoids in the plant, such as cannabidiol (CBD), have unique properties. Given that CBD can modulate the undesirable effects of THC, therapeutic agents, such as nabiximols, contain higher CBD:THC ratios than illicit marijuana. We tested the hypothesis that THC impairs a relevant cognitive function for long-term success, namely willingness to exert cognitive effort for greater rewards, and that CBD could attenuate such decision-making impairments. METHODS: Male Long–Evans rats (n = 29) performing the rat cognitive effort task (rCET) received acute THC and CBD, independently and concurrently, in addition to other cannabinoids. Rats chose between 2 options differing in reward magnitude, but also in the cognitive effort (attentional load) required to obtain them. RESULTS: We found that THC decreased choice of hard trials without impairing the animals’ ability to accurately complete them. Strikingly, this impairment was correlated with CB1 receptor density in the medial prefrontal cortex — an area previously implicated in effortful decision-making. In contrast, CBD did not affect choice. Coadministration of 1:1 CBD:THC matching that in nabiximols modestly attenuated the deleterious effects of THC in “slacker” rats. LIMITATIONS: Only male rats were investigated, and the THC/CBD coadministration experiment was carried out in a subset of individuals. CONCLUSION: These findings confirm that THC, but not CBD, selectively impairs decision-making involving cognitive effort costs. However, coadministration of CBD only partially ameliorates such THC-induced dysfunction.